No bestiário dos campos, a animalização do homem: Primo Levi, Yoram Kaniuk, Art Spiegelman - Filipe Amaral Rocha de Menezes (2023)
This dissertation intends to investigate the narrative of the animalization of man in the Holocaust literature in selected texts of Primo Levi, Yoram Kaniuk and Art Spiegelman. The metaphorical sense of animalization that happened in the Shoah returns in Levi’s reports in a resumption of terms and the dehumanizing language of the Nazis, used in his texts as a form of resistance and denunciation to characterize the condition of the prisoner, his behavior, his attempts to survive. The narrative elements of Primo Levi’s survivor testimonies in which he portrays the animalized condition of men would be present in literature and other arts, constituting a narrative strategy. In addition, due to their memorialistic character, these testimonies of the animalization of man constituted a tribute to the victims and a manifesto against contemporary intolerance and hate speech. Taking Levi's reports and his reflection in The Drowned and the Saved, I demonstrate how the striking elements of the testimony narrative are shaped in Yoram Kaniuk’s novel Adam Resurrected, with his character Adam Stein, the clown-dog touched by madness, and in Art Spiegelman’s graphic novel Maus, as the testimony of the trauma of the author-narrator and the experience of his father, Vladek Spiegelman. These literary works would be inscribed as an aesthetic of the animalization of man in the Shoah. Relying on a critical fortune, an attempt was made to analyze the literary corpus taking into account the following objectives: to delimit a concept of animalization in the literature on the Shoah; discuss the elements of the animalization of man in If This Is a Man of Primo Levi; to study the canine metamorphosis of the protagonist of Adam Resurrected, by Yoram Kaniuk and the stereotypes of the characters and their caricaturizing in Maus, by Art Spiegelman; and finally, build a critical reflection on animalization and human degradation in testimonial literature.